Dissemination of Cryphonectria parasicita (Murr.) Barr fungus, and the possibilities of protection of a chestnut orchard in Romania - Kovács, Gabriella; Bodnár, Dominika; Radócz, László (GEORGIKON FOR AGRICULTURE, 2019)
The chestnut plantation, which have been regularly visited for more than three years, located at the outskirt of Salard village. It lies less than 30 kilometers from the Hungarian-Romanian border. On the family farm initially 2 hectares of chestnut were planted, which has now expanded to 4 hectares. However, some of the propagation materials from Italy have already been infected with chestnut blight. Thanks to early intervention, the amount of treatments required has decreased considerably. Also in this plantation the presence of chestnut gall-wasp (Dryocosmus kuriphilus Yasumatsu) was first detected in Romania by our group. By this time its spread has been managed to stop. This plantation exemplifies well how diseases and pests can spread easily through the absence of plant protection control.
Keywords: chestnut; Cryphonectria parasitica; chestnut blight; chestnut plantation; Dryocosmus kuriphilus